Localization Of MMP-2 And MMP-9 In Canine Mammary Gland During Pregnancy - Despina Pupaki; Dessislava Ankova; Veselin Vasilev; Pavel Rashev (Journal of Biomedical & Clinical Research)
The mammary gland is unique in its development because most of its branching occurs in adolescent rather than in prenatal development. During early pregnancy extensive ductal side branching occurs while during the second half, secretory lobuloalveolar units are formed within the mammary gland. As modulators of the extracellular matrix, matrix metalloproteinases (MMPs) are the major enzymes taking part in the development of the gland. The activity of MMP-2 and MMP-9 has mostly been associated with tumor progression, while their participation in the physiological development of the mammary gland is not well characterized. In the present study the cell-specific localization of MMP-2 and MMP-9 in the developing dog mammary gland during pregnancy was investigated. In the early stages, both gelatinases were present, being located mostly in the epithelium of the ducts and less so in the surrounding stroma. After the formation of alveoli, MMP-2 was still present but MMP-9 was absent from the glandular epithelium and the stroma, being present only in the epithelium of the larger ducts. The results show that most likely, both gelatinases take part in ductal branching during early pregnancy, but only MMP-2 is associated with the differentiated stage of lactation.